EMPLOYING CASE TECHNOLOGY TO IMPROVE SPEAKING SKILLS IN EFL CLASSES - Bakhieva, M.T. (ILIM hám JÁMIYET, 2023)
This article describes the importance and use of the case method in the process of teaching a foreign language in order to develop the professional communicative competence of students in the EFL classrooms. The article presents the possibilities of this educational technology, the goals of the cases, the stages of working with them, as well as practical recommendations. The author concludes that development of case technologies, based on learning by solving specific problems of situations will be carried out if the practical goal of organizing teaching is defined as improving communicative competence.